Eosinophilic fasciitis – a case report - Wisłowska, Małgorzata; Rok, Mariusz; Matuszyk, Maciej (Reumatologia/Rheumatology, 2005)
Eosinophilic fasciitis is a rare disease of a connective tissue. We have presented a case report of the patient with EF, and described treatment methods, which eventually proved to be a success.